A Pickering emulsion route to a stearic acid/graphene core–shell composite phase change material. (April 2016) - Dao, Trung Dung; Jeong, Han Mo
Abstract: Stearic acid (SA) is encapsulated by a water-dispersible graphene functionalized with poly(vinyl alcohol) using an eco-friendly Pickering emulsion route to prepare a novel shape-stabilized phase change composite for thermal energy storage. In the method, the oil phase of melted SA can be easily encapsulated and stabilized by the graphene Pickering stabilizer in an aqueous medium. The subsequent solidification of the SA cores allows the formation of the shape-stabilized phase change composite microcapsules. The composite has an active phase changeable SA core for thermal energy storage via latent heat, and an ultra-thin graphene shell to prevent leakage of the SA core at liquid state during phase transition. The shape stability is achieved at a very low graphene content of around 1 wt%, giving an ultra-high content of the active SA core of up to around 99 wt% for maximizing the energy storage capacity of the composite. In addition, thermal conductivity of the composite is enhanced due to the thermally conductive graphene shell. Moreover, the graphene shell having excellent thermal stability and barrier property effectively serves as a protective layer for the SA core for improving thermal stability of the composite.